THE SENSITIVITY AND SPECIFICITY OF FLOTATION AND SEDIMENTATION METHODS FOR SOIL-TRANSMITTED HELMINTHS (STH) IN THE FECES OF VEGETABLE FARMERS IN NGAGLIK DISTRICT, YOGYAKARTA - Pratiwi, Cyntia Rizkiana; Putri, Novita Eka (Politeknik Medica Farma Husada Mataram, 2024)
Worm infection is a public health problem due to poor sanitation and behavior, and it can affect various age groups and professions, including vegetable farmers. Ngaglik Subdistrict is an area with water absorption, making it susceptible to becoming a center for the development of Soil-Transmitted Helminths (STH). STH detection can be done through laboratory examinations using flotation and sedimentation methods. The research aimed to determine the differences in sensitivity and specificity between the flotation and sedimentation methods for STH detection in vegetable farmers in Ngaglik District, Yogyakarta. The research method used was analytical observational with a cross-sectional approach, utilizing interview data and laboratory examinations. Random sampling was used, resulting in 18 samples. The research findings of 18 fecal samples using two testing methods showed that 8 samples were positive for STH infection. Positive samples for the flotation and sedimentation methods were 4 (22.2%) and 5 samples (27.8%), respectively. The sensitivity of the flotation method was higher than that of sedimentation, namely 25% and 20%. The specificity of the flotation and sedimentation methods was 71.4% and 77%, respectively. The McNemar test results showed no significant difference in the sensitivity and specificity between the flotation and sedimentation methods (0.109 > 0.05%), indicating that both methods can be used for STH detection in a laboratory setting.